2021
DOI: 10.2196/26022
|View full text |Cite
|
Sign up to set email alerts
|

Using the Computer-based Health Evaluation System (CHES) to Support Self-management of Symptoms and Functional Health: Evaluation of Hematological Patient Use of a Web-Based Patient Portal

Abstract: Background Patient portals offer the possibility to assess patient-reported outcome measures (PROMs) remotely, and first evidence has demonstrated their potential benefits. Objective In this study, we evaluated patient use of a web-based patient portal that provides patient information and allows online completion of PROMs. A particular focus was on patient motivation for (not) using the portal. The portal was developed to supplement routine monitoring … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 33 publications
1
8
0
2
Order By: Relevance
“…Considering that the average completion time of the paper-pencil version of the QLQ-C30 is around 11 minutes [ 54 ], this highlights that ePRO assessments can be more time-efficient and potentially easier to use if support is supplied to those patients who need it. The average completion time of 4.9 (SD 3.20) minutes is similar to other studies that measured the time of electronic completion for the QLQ-C30 [ 55 , 56 ]. Another finding was that patients needed less time to complete the questionnaire at the second assessment, indicating a potential learning effect.…”
Section: Discussionsupporting
confidence: 81%
“…Considering that the average completion time of the paper-pencil version of the QLQ-C30 is around 11 minutes [ 54 ], this highlights that ePRO assessments can be more time-efficient and potentially easier to use if support is supplied to those patients who need it. The average completion time of 4.9 (SD 3.20) minutes is similar to other studies that measured the time of electronic completion for the QLQ-C30 [ 55 , 56 ]. Another finding was that patients needed less time to complete the questionnaire at the second assessment, indicating a potential learning effect.…”
Section: Discussionsupporting
confidence: 81%
“…PROMs are administered through the Computer-based Health Evaluation System (CHES) using a remote, web-based patient portal, in which patients complete PROMs before and during patient visits at the outpatient unit [ 21 ]. In the portal, patients can access their scores and corresponding self-management advice [ 20 ]. The PROMs assessment is part of the Austrian Myeloma Registry (AMR) [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…PROMs are completed either remotely before or during patients’ visits every few weeks at the outpatient unit. We found that symptom monitoring is feasible and relevant for patients with Multiple Myeloma [ 19 , 20 ]. Patients’ feedback, however, suggested that more regular assessments supported by reminders and systematic screening of the results by health care professionals in-between patient visits could increase adherence and patient experience [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The eDiary was developed to enable the comprehensive patient-reported assessment of FI and bowel movements in clinical routine and for clinical trials. We used the Computer-based Health Evaluation System (CHES) [ 26 28 ] as a software basis to develop an iOS and Android app that can be downloaded on most mobile devices. Alternatively, the app can also be accessed via any web browser (no installation needed), although this way it does not offer all of the same features (e.g., no push notifications).…”
Section: Methodsmentioning
confidence: 99%